Potential barriers and facilitators for implementation of an integrated care pathway for hearing-impaired persons: an exploratory survey among patients and professionals - Verschuure Hans; Joore Manuela A; van der Horst Frans; Grutters Janneke PC; Dreschler Wouter A; Anteunis Lucien JC (BMC, 2007)
Abstract Background Because of the increasing costs and anticipated shortage of Ear Nose and Throat (ENT) specialists in the care for hearing-impaired persons, an integrated care pathway that includes direct hearing aid provision was developed. While this direct pathway is still under investigation, in a survey we examined expectations and potential barriers and facilitators towards this direct pathway, of patients and professionals involved in the pathway. Methods Two study populations were assessed: members of the health professions involved in the care pathway for hearing-impaired persons (general practitioners (GPs), hearing aid dispensers, ENT-specialists and clinical audiologists) and persons with hearing complaints. We developed a comprehensive semi-structured questionnaire for the professionals, regarding expectations, barriers, facilitators and conditions for implementation. We developed two questionnaires for persons with hearing complaints, both regarding evaluations and preferences, and administered them after they had experienced two key elements of the direct pathway: the triage and the hearing aid fitting. Results On average GPs and hearing aid dispensers had positive expectations towards the direct pathway, while ENT-specialists and clinical audiologists had negative expectations. Professionals stated both barriers and facilitators towards the direct pathway. Most professionals either supported implementation of the direct pathway, provided that a number of conditions were satisfied, or did not support implementation, unless roughly the same conditions were satisfied. Professionals generally agreed on which conditions need to be satisfied. Persons with hearing complaints evaluated the present referral pathway and the new direct pathway equally. Many, especially older, participants stated however that they would still visit the GP and ENT-specialist, even when this would not be necessary for reimbursement of the hearing aid, and found it important that the ENT-specialist or Audiological Centre evaluated their hearing aid. Conclusion This study identified professional concerns about the direct pathway for hearing-impaired persons. Gaps exist in expectations amongst professions. Also gaps exist between users of the pathway, especially between age groups and regions. Professionals are united in the conditions that need to be fulfilled for a successful implementation of the direct pathway. Implementation on a regional level is recommended to best satisfy these conditions.